Kerapatan dan Keanekaragaman serta Kondisi Terkini Ekosistem Lamun di Perairan Pulau Ponelo - Ismail, Zulkifli; Kasim, Faizal; Panigoro, Citra (The NIKe Journal, 2023)
This research aims to determine the density, diversity and dominance index as well as the current condition of the seagrass ecosystem in Ponelo Village, Ponelo Islands District, North Gorontalo Regency. This research was carried out from March to August 2019. Samples were collected using the line transect method in a systematic manner using 1x1 meter quadrants. All research study areas are divided into 3 stations based on the presence of seagrass. Data analysis includes density, diversity and dominance index as well as current conditions. There were 4 types of seagrass found at the research location from 2 families, namely Enhalus acroides and Cymodocea rotundata from the Potomogetonaceae family and Halophila ovalis and Thalassia hemprichii from the Hydrocharitaceae family. The type of seagrass that has the highest density is Cymodocea rotundata and the type of seagrass that has the lowest density is Halophila ovalis. Seagrass diversity was obtained at stations 1 and 2 with a value of 0.98-0.91 with low status, while station 3 obtained a value of 1.38 with medium status. The Dominance Index results from stations 1, 2, and 3 obtained a value of 0.25-0.50 in the low category. The condition of the seagrass beds is based on density values, namely that the conditions at stations 1, 2 and 3 are rather dense and sparse.